Pengembangan Media Pembelajaran Articulate Storyline 3 Berbasis Problem Based Learning Pada Tema 6 Energi Dan Perubahannya Kelas III SD - Siti Nurjannah; Nila Lestari (Journal on Education, 2023)
This research aims to: (1) determine the development of Articulate Atoryline 3 learning media based on Problem Based learning on theme 6 energy and its changes in elementary school. (2) determine the feasibility of Articulate Storyline 3 media based on Problem Based Learning on theme 6 energy and its changes. This research is a type of development research using the ADDIE model which consists of 5 stages of Analysis, Design, Development, Implementation, Evaluation. The subject of this research was the Articulate Storyline 3 learning media. The instruments used were validation questionnaires for media experts, material experts, teacher responses and student responses. The data analysis techniques used in this research are qualitative descriptive analysis techniques and quantitative analysis. From the validation results, the average for media experts was 83.6%, from validation, the average for material experts was 88%, from the response results, the average for teacher responses was 100%, and from the results of student responses, the average for student response was 84.5%. Based on the results of the data above, an average percentage of the feasibility of problem-based learning media for Articulate Storyline 3 based on problem-based learning is 89%, which can be categorized as very good. So it can be concluded that the learning media in the Articulate Storyline 3 application based on Problem Based Learning theme 6 energy and its changes for class III elementary school can be said to be "very good" to be applied as learning media during the learning process